2013
DOI: 10.1179/2047773213y.0000000074
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intestinal parasitosis, anaemia, and malnutrition among school children in Ethiopia

Abstract: Research on associated risk factors for intestinal parasitic infections and malnutrition in various geographic regions is needed for the development of appropriate control strategies. The aim of this study was to determine the risk factors associated with intestinal parasitic infections, anaemia, and malnutrition in school children, living in urban and rural areas of northern Ethiopia. Six hundred school children, aged 6-15 years, were randomly selected in a cross-sectional survey from 12 primary schools. Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
65
8
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 23 publications
16
65
8
3
Order By: Relevance
“…No similar study was obtained to compare our finding with; however, 11% prevalence was reported from Northern part of Ethiopia [15]. The larger regional variation might be due to differences in geographical variation and differences in life style.…”
Section: Discussionmentioning
confidence: 55%
“…No similar study was obtained to compare our finding with; however, 11% prevalence was reported from Northern part of Ethiopia [15]. The larger regional variation might be due to differences in geographical variation and differences in life style.…”
Section: Discussionmentioning
confidence: 55%
“…Migration from a rural to an urban area in Senegal was positively associated with HAZ and WHZ . Finally, two studies reported the adverse effects of poor personal hygiene practices on stunting and underweight …”
Section: Resultsmentioning
confidence: 97%
“…Generally, increasing age was found to be a risk factor for anemia, vitamin D deficiency, and folate deficiency among male and female adolescents. Likewise, studies in Nigeria, India, and South Korea found increasing age to be inversely associated with plasma retinol, Hb, and serum 25(OH)D, respectively, for both sexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of this study is that it rigorously assessed the impact of simple hygiene measures on the incidence of new infection and anaemia in the study population. Prior RCTs have assessed the impact of handwashing on diarrhoea and respiratory tract infections among children in developing countries1 and there have been observational studies on the relationship of hygiene with parasitic infection 2 3…”
Section: Commentarymentioning
confidence: 99%